Examining the Effects of the TASER on Cognitive Functioning, Arizona, 2012-2013 - White, Michael D. ([Verlag nicht ermittelbar], 2017)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. These data were collected as part of an effort to investigate the effects of the TASER on cognitive functioning. To explore this issue, the authors carried out a pilot study with 21 police recruits who received a TASER exposure as part of their training at the San Bernardino County (CA) Training Center. Following the pilot study, the researchers conducted a Randomized Controlled Trial (RCT) where healthy human volunteers were randomly assigned to four groups, two of which received a TASER exposure. Participants completed a battery of cognitive tests before and after receiving their assigned treatment.